The Personality of Bapang Jaya Sentika in the Movements of the Bapang Mask Dance as a Dynamic Visual Expression - Ananda Eka Jossy Saputra; Abdul Rahman Prasetyo (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
This research is motivated by the visual and symbolic diversity of the Bapang Malangan Mask Dance, especially the character of Bapang Jaya Sentika who has a firm, dominant character, and is full of inner conflict, but until now the character's personality has not been fully represented through conventional visual documentation that tends to be static. The explosive, rhythmic, and energetic movements of the Bapang Mask Dance contain psychological dimensions that can only be understood through visual representations that are able to capture the dynamics of time and the overall flow of the movements. This research aims to reveal, represent, and visualize the personality of the Bapang Jaya Sentika Character in the Bapang Mask Dance movements as a dynamic visual expression through the creation of photographic artworks. The research methodology uses a practice-based research approach with the I Made Bandem artistic creation model which includes the stages of preparation, elaboration, synthesis, realization, and completion, where the process of exploring dance movements, experimenting with long exposure photography techniques, and visual reflection are the main sources of research data. The results of the study indicate that the long exposure photography technique is able to represent the personality of Bapang Jaya Sentika more expressively and symbolically through light trails that depict the ego, inner struggle, self-control, and determination of the character. The six photographic works produced prove that a dynamic visual approach can bring new meaning to the Bapang Mask Dance movement while enriching the documentation and preservation strategies for traditional performing arts in the digital visual era.